Human Pluripotent Stem Cells Go Diabetic: A Glimpse on Monogenic Variants - Heller, Sandra; Melzer, Michael Karl; Azoitei, Ninel; Julier, Cécile; Kleger, Alexander (Frontiers in Endocrinology, 2021)
Diabetes, as one of the major diseases in industrial countries, affects over 350 million people worldwide. Type 1 (T1D) and type 2 diabetes (T2D) are the most common forms with both types having invariable genetic influence. It is accepted that a subset of all diabetes patients, general-ly estimated to account for 1-2% of all diabetic cases, is attributed to mutations in single genes. As only a subset of these genes has been identified and fully characterized, there is a dramatic need to understand the pathophysiological impact of genetic determinants on -cell function and pancreatic development but also on cell replacement therapies. Pluripotent stem cells differentiated along the pancreatic lineage provide a valuable research platform to study such genes. This review summarizes current futures perspectives in applying this platform to study monogenic diabetes variants.